Placental Cannabinoid Receptor Expression in Preterm Birth - Stepan Feduniw; Izabela Krupa; Katarzyna Łagowska; Piotr Laudański; Jacek Tabarkiewicz; Barbara Stawarz; Grzegorz Raba (Journal of Pregnancy)
Conclusions: The presence of CBR mRNA in the human placental tissue was confirmed. The decreased expression of CBRs could serve as an indicator in predicting PTB.